ENHANCING EDUCATIONAL EFFECTIVENESS AND CREATIVE ACTIVITY THROUGH PAINTING - Boboqulova Adiba Husanovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the role of painting in enhancing both educational effectiveness and students’ creative activity. Painting encourages active engagement, imaginative thinking, and problem-solving skills within the learning process. By incorporating visual arts into lessons, teachers can create a dynamic, interactive environment that stimulates creativity, critical thinking, and motivation. The article discusses methods for integrating painting into various subjects to improve learning outcomes and foster creative expression. The findings demonstrate that painting-based activities contribute significantly to both cognitive and creative development, making them an essential component of modern education.